Rapid Detection of Campylobacter jejuni in Poultry Products Using QD-FRET Based Fluoroimmunoassay - Wang buh, Hong; Slavik, Michael; Li, Yanbin; Wang, Andrew (International Journal of Poultry Science, 2015)
Campylobacter jejuni is one of the leading causes of foodborne human gastrointestinal disease worldwide. Poultry and poultry products have been identified as the major transmission routes to humans for this pathogenic bacterium. The objective of this research was to develop a rapid and sensitive method for detection of C. jejuni in chicken carcasses and ground turkey using quantum dots (QDs)-fluorescence resonance energy transfer (FRET) based fluoroimmunoassay. In the experiments, two multicolor QDs with the emission wavelengths of 530 nm (QDs 530) and 580 nm (QDs 580) were conjugated with rabbit anti-C. jejuni antibody (primary antibody Ab1) and goat anti-rabbit IgG antibody (secondary antibody Ab2) to serve as energy donors and acceptors, respectively. When the conjugated QDs 530 and QDs 580 were mixed, energy transfer occurred through FRET, causing the detectable fluorescence signal of the acceptor to be increased. When C. jejuni was present, donors would bind to the target bacteria and then the acceptors could bind to the donors, resulting in FRET in signal transduction. Poultry samples were spiked with C. jejuni at different concentrations and then, the magnetic nanobeads (MNB) coated with anti-C. jejuni antibody were added to the samples to capture the target bacteria. After magnetically separating the MNB-C. jejuni complexes from food matrices, the complexes were mixed with the QDs 530 and incubated for 30 min. Finally, the QDs 580 were added to bind the QDs 530 for FRET and the fluorescent intensity was measured using a spectrophotometer. The results showed that the fluoroimmunoassay could rapidly detect C. jejuni in poultry products with a detection limit of 30-50 cfu/ml and the total detection time of less than 2 hours. This highly adaptive and flexible technique could provide the poultry industry a more rapid and effective method for detection of major foodborne pathogens in poultry products.